PERSEPSI GURU TENTANG KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DI SMA NEGERI SE-KOTA SAWAHLUNTO - Pri Sisilia Windy; Nellitawati Nellitawati; Lusi Susanti; Widiawati Widiawati (STKIP Pesisir Selatan, 2026)
Objective: Transformational leadership among school principals is an important factor in supporting educational quality improvement through motivation, exemplary behavior, encouragement of innovation, and attention to teachers’ needs. This study aimed to describe teachers’ perceptions of principals’ transformational leadership in public senior high schools throughout Sawahlunto City based on four dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The study employed a quantitative approach with a descriptive method. The population consisted of 84 teachers, all of whom were selected as respondents using total sampling. Data were collected through a four-point Likert-scale questionnaire consisting of 50 items that had been declared valid and reliable. The data were analyzed descriptively using mean scores. The results showed that teachers’ perceptions of principals’ transformational leadership were categorized as good, with an overall mean score of 3.24. Across the four dimensions, idealized influence obtained a mean score of 3.23, inspirational motivation 3.24, intellectual stimulation 3.27, and individualized consideration 3.21. These findings provide empirical evidence regarding the implementation of principals’ transformational leadership and may serve as input for strengthening leadership practices in public senior high schools in Sawahlunto City.